Analysis of Language Errors in News on Tribun Timur.com: Morphology - Hasniar Lukman; Saifullah; Kamal; Aswadi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research employs a qualitative descriptive method aimed at analyzing spelling and morphological errors in online news articles published by Tribun Timur.com, specifically the Tribun Sidrap edition dated February 3, 2025. The study focuses on language errors involving the use of letters, word formation, affixation, punctuation, and other elements related to the Indonesian Spelling System (EYD) Edition V. A total of 25 news articles were selected purposively as the data source. The data were collected through reading, note-taking, and documentation techniques, and analyzed using data reduction, classification, and interpretation procedures. The findings reveal several types of language errors, including seven errors in the use of capital letters, three italicization errors, five-word formation errors, nine affixation mistakes, five hyphenation or compound word errors, one error in preposition use, three numerical/punctuation issues, and two comma-related punctuation errors. These mistakes suggest a lack of adherence to standardized Indonesian language rules in the media, which could affect the credibility of news articles and influence public language habits. The study concludes that consistent application of EYD rules is essential to improve the quality of language in online news writing. It recommends that journalists and editors implement rigorous editing practices to reduce errors and promote accurate language use. Furthermore, future research is encouraged to explore broader linguistic aspects such as syntactic and semantic errors in various media formats to support national language development and public literacy.